1987
DOI: 10.1007/bf00215533
|View full text |Cite
|
Sign up to set email alerts
|

Electron-microscopic studies on the presence of gap junctions between corneal fibroblasts in rabbits

Abstract: Corneal fibroblasts, major cellular components of the corneal stroma, are loosely arrayed between collagen lamellae. They play an important role in the metabolic and physiological homeostasis mechanisms by which the cornea is kept transparent. This paper deals with the demonstration of the gap junctions between the corneal fibroblasts of rabbits by transmission electron microscopy of thin sections and of freeze-fracture specimens. Under the transmission electron microscope, the corneal fibroblasts are seen bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 3 publications
0
29
0
1
Order By: Relevance
“…These cells also transformed and became elongated and spindleshaped, with long processes that extended and developed gap junctions with neighboring cells (Nishida et al, 1988). The ultrastructure of keratocytes in collagen gels resembles that found in normal keratocytes in vivo (Ueda et al, 1987). Langholtz and co-workers investigated collagen lattice contraction by the skin fibroblasts in this three-dimensional in-vitro model (Langholtz et al, 1995), and other researchers have studied the regulation of collagen and collagenase gene expression by skin fibroblasts in a collagen gel (Mauch et al, 1988(Mauch et al, , 1989.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These cells also transformed and became elongated and spindleshaped, with long processes that extended and developed gap junctions with neighboring cells (Nishida et al, 1988). The ultrastructure of keratocytes in collagen gels resembles that found in normal keratocytes in vivo (Ueda et al, 1987). Langholtz and co-workers investigated collagen lattice contraction by the skin fibroblasts in this three-dimensional in-vitro model (Langholtz et al, 1995), and other researchers have studied the regulation of collagen and collagenase gene expression by skin fibroblasts in a collagen gel (Mauch et al, 1988(Mauch et al, , 1989.…”
Section: Discussionmentioning
confidence: 88%
“…In the corneal stroma, keratocytes are embedded in extracellular matrix proteins, mainly type I collagen ; the cells' functions are continuously modulated by interaction with this extracellular matrix. Thus, threedimensional culture of keratocytes in collagen gel represents the conditions more closely related to the situation in vivo than does monolayer culture (Ueda et al, 1987 ;Nishida et al, 1988). The present study used this model to examine the inhibitory action of Galardin on collagen degradation by keratocytes.…”
Section: Introductionmentioning
confidence: 97%
“…The existence of gap junctions between fibroblasts in the rabbit cornea (VEDA et al, 1987) and between fibroblast-like cells in the guinea-pig small intestine (ZHou et al, 1992) has been reported. However, several investigators found no junctions between the fibroblasts in the myotendon in previous studies (GELBER et al, 1960;MACKAY et al, 1969;NAKAO,1976;TROTER et al, 1981), while others found intermediate junctions of the zonula adherens type between fibroblasts in the rat flexor digital tendon and in the rat tendon tail (FARQUHAR and PALADE, 1963;GREENLEE and Ross, 1967;SQUIER and BAUSCH, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of rat or rabbit cornea by transmission and scanning electron microscopy have shown the corneal keratocytes to be flattened, polygonal cells, and had cytoplasmic processes. The processes of neighboring keratocytes contacted each other to form an extensive and continuous network structure (Ueda et al, 1987;Nishida et al, 1988). These morphological characteristics of keratocytes closely resemble that of the GFP(1) cells observed in this study.…”
Section: Discussionmentioning
confidence: 99%